Strengthening the Development of Performance and Competitiveness of MSMES Through the BTN Syariah Halal Certification Facilitator Program in Jember Regency - Siti Khayisatuzahro Nur; Muhammad Syafi'i (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025